Orbital angular momentum in an driven optical parametric oscillator - Rodrigues de Souza, Carlos Eduardo (2018)
The control of the Orbital Angular Momentum (OAM) of light in quantum optical system can provide an additional degree of freedom, that can enable many applications in quantum mechanics and optical communications. Lasers beams with OAM (optical vortices) are generally described by Laguerre-Gaussian modes, which have a doughnut intensity distribution with phase singularities in the wavefront. In the special case of first order OAM modes, the Poincaré sphere gives a convenient geometrical representation of those optical vortices. Following the theoretical proposal done by B.Coutinho dos Santos et. al in 2007, in this project we are interested in studying experimentally the dynamics of an Optical Parametric Oscillator under the injection of a seed beam with OAM. The main aim of this project is to characterize the OAM conservation in the twin beams, namely signal and idler, coming from the injected Optical Parametric Oscillator, according to the symmetry in the Poincaré sphere. We aim also at studying theoretically the dynamics of the twin beams generated, according to the real experimental parameters of the setup, to improve the twin beams creation efficiency, which will enable us to study experimentally quantum entanglement in this apparatus. Also, in the scope of this work, the measurements and characterization of squeezing was performed in the recent mounted OPO at UFF.